(r) we there yet? The change to rhoticity in New York City English. (16th June 2014) - Becker, Kara
Abstract Labov (1966, 1972b) described the variable production of coda /r/ in New York City English (NYCE) as a change in progress from above in the direction of rhoticity. Since then, scholars have commented on the slow rate of change toward rhoticity in NYCE and characterized (r) as a superposed feature restricted to formal speech (Fowler, 1987; Labov, 1994; Labov, Ash, & Boberg, 2006). This study's ethnically diverse sample of speakers from the Lower East Side of Manhattan (n = 65) shows a mean rate of /r/ production of 68%, with young people, women, and middle-class speakers leading in the production of /r/ in apparent time. Speakers from five ethnic backgrounds—African American, Chinese, Jewish, Puerto Rican, and white—show coherence for the internal constraints on variable nonrhoticity. However, only Chinese, Jewish, and white speakers participate in the change toward rhoticity. These findings highlight the role of ethnicity in patterns of variation and change and demonstrate that the change toward rhoticity in NYCE has accelerated and is no longer restricted to formal speech.